1996
DOI: 10.1366/0003702963906410
|View full text |Cite
|
Sign up to set email alerts
|

Important Aspects concerning the Quantification of Biomolecules by Time-of-Flight Secondary-Ion Mass Spectrometry

Abstract: Fundamental aspects regarding the use of time-of-flight secondary-ion mass spectrometry (TOF-SIMS) as a quantitative tool for the analysis of organic compounds are reported. The following factors are discussed: (1) the use of Poisson's law to correct for dead-time in single-ion data collection; (2) practical considerations concerning the analysis of “real world” samples; and (3) the effect of the etching process on the reproducibility of the intensity ratio (analyte/internal standard) of Ag-cationized species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In contrast, the CsA system (i.e., where the substrate is crucial for ionization) indicated that there was no sampling error for Ag substrates etched under identical conditions, but that there was a sampling error for Ag etched under similar conditions (107). Because the peak intensities of the Ag-cationized CsA species are substantially lower than those for cocaine, the precision of a peak area measurement is poorer.…”
Section: Preparation Of Metal Substratesmentioning
confidence: 98%
See 4 more Smart Citations
“…In contrast, the CsA system (i.e., where the substrate is crucial for ionization) indicated that there was no sampling error for Ag substrates etched under identical conditions, but that there was a sampling error for Ag etched under similar conditions (107). Because the peak intensities of the Ag-cationized CsA species are substantially lower than those for cocaine, the precision of a peak area measurement is poorer.…”
Section: Preparation Of Metal Substratesmentioning
confidence: 98%
“…This increase is followed by an exponential decrease in the CsA SI yield when the concentration is increased from 0.5 mg/mL to 80 mg/mL (region 11). to 0.5 mg/mL (region I), and steadily decreases throughout region 11 (107). Several factors can be considered to play a role in determining the shape of these molecular SI yield curves.…”
Section: Dependence Of Secondary Ion Emission On Surjiace Coveragementioning
confidence: 99%
See 3 more Smart Citations